Biomechanical comparison of five fixation methods in minimally invasive hallux valgus osteotomy: a three-dimensional finite element analysis - Li, Xiaomei; Zhang, Lan; Wang, Jiandong; Wang, Yongjun; Dai, Guangming; Jiang, Wei; Zheng, Haoyan; Feng, Bo; Tian, Weiqing (Frontiers in Medicine, 2025)
ObjectiveAlthough minimally invasive osteotomy for hallux valgus employs a variety of internal fixation methods, systematic biomechanical evidence evaluating the stability and strength of different fixation configurations is lacking. This study aimed to quantitatively compare the biomechanical properties of five internal fixation techniques using three-dimensional finite element analysis.MethodsBased on CT data of the foot of an adult female patient with moderate hallux valgus (HVA 27.6°, IMA 12.4°), a finite element model of the post-osteotomy state was constructed. The following fixation schemes were simulated: Group A: two 3.5 mm beveled metal screws; Group B: one 3.5 mm beveled metal screw; Group C: two 2.0 mm Kirschner wires; Group D: one 3.5 mm beveled metal screw and one 2.0 mm Kirschner wire; Group E: three 2.0 mm Kirschner wires. Comparison parameters included the maximum equivalent (Von-Mises) stress between the osteotomy fragment and the internal fixation, the maximum displacement of the osteotomy fragments in the X, Y, and Z axes, and the overall displacement of the internal fixation.ResultsUnder the same load: 1. Maximum stress of the osteotomy fragment: Group A (5.6824 MPa) < Group B < Group D < Group C < Group E (33.33 MPa); 2. Maximum stress of internal fixation: Group A (16.159 MPa) < Group D < Group B < Group C < Group E (238.68 MPa, with significant stress concentration); 3. Maximum displacement of the osteotomy fragment (X/Y/Z): Group E (4.2035/2.8512/7.1309 mm) < Group D < Group A < Group C < Group B (4.3251/3.2353/7.4102 mm); 4. Overall displacement of internal fixation: Group B (7.5284 mm) < Group D < Group C < Group A < Group E (7.9256 mm).Conclusion1. Two 3.5 mm beveled screws (Group A) are the optimal configuration, combining low stress distribution (lowest stress on the osteotomy fragment and internal fixation) with high stability (moderate displacement); 2. Combined fixation (Group D) is a secondary option, but bone quality assessment is required (Kirschner wire fixation carries the risk of loosening); 3. Three Kirschner wires (Group E) are only suitable for low-load cases due to the risk of high stress concentration (238.68 MPa).